Growth performance, feed utilization and body composition of advanced nursing Nile tilapia (Oreochromis niloticus) fed diets containing Black Soldier Fly (Hermetia illucens) larvae meal. (22nd June 2017) - Devic, E.; Leschen, W.; Murray, F.; Little, D.C.
Abstract: A 32‐day experiment was conducted to evaluate the effects on the performance, feed utilization efficiency and body composition of a strategic inclusion of Black Soldier Fly larvae meal (MM) in a commercially formulated diet for advance nursing Nile tilapia ( Oreochromis niloticus ). Four isonitrogenous and isoenergetic diets were commercially formulated and manufactured as a control and three test diets with strategic inclusions of MM inclusions (0, 30, 50 and 80 g/kg) and poultry by‐product meal substituting gradually three conventional expensive feedstuffs: fish meal, fish oil and soybean meal. Fish (5.7 ± 0.5 g/fish) were nursed in a cage‐in‐lake system (Volta Lake, Ghana), under conditions similar to commercial farming practices. Control and experimental diets were fed to triplicate cages by hand to visual satiety, six times per day. Growth performance (final weight; weight gain and SGR), feed utilization efficiency indices (FCR and PER) and feed intake were not significantly different ( p  ≥ .05) between treatments. Survival was significantly different ( p  < .05) but more likely explained by the stress related to frequent handling on the smaller fish. Fish whole body composition (dry matter, crude protein, lipid, ash and fibre) was unaffected by the treatment ( p  ≥ .05), except for the fatty acid compositions which mirrored that of the diets.